2010
DOI: 10.1016/j.neuropharm.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Early developmental alterations in GABAergic protein expression in fragile X knockout mice

Abstract: The purpose of this study was to examine the expression of GABAergic proteins in Fmr1 knockout mice during brain maturation and to assess behavioural changes potentially linked to perturbations in the GABAergic system. Quantitative western blotting of the forebrain revealed that compared to wild-type mice, the GABA A receptor α1, β2, and δ subunits, and the GABA catabolic enzymes GABA transaminase and SSADH were down-regulated during postnatal development, while GAD65 was up-regulated in the adult knockout mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 168 publications
(229 reference statements)
5
113
1
Order By: Relevance
“…Decreased GABA A receptor expression and function has been demonstrated in FMR1 knockout mice (El Idrissi et al, 2005;D'Hulst et al, 2006D'Hulst et al, , 2009Curia et al, 2009;Adusei et al, 2010;Olmos-Serrano et al, 2010). We have also recently demonstrated that GABA B R1 expression is down-regulated in the forebrains of immature and mature FMR1 mice compared with wild-type mice .…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Decreased GABA A receptor expression and function has been demonstrated in FMR1 knockout mice (El Idrissi et al, 2005;D'Hulst et al, 2006D'Hulst et al, , 2009Curia et al, 2009;Adusei et al, 2010;Olmos-Serrano et al, 2010). We have also recently demonstrated that GABA B R1 expression is down-regulated in the forebrains of immature and mature FMR1 mice compared with wild-type mice .…”
Section: Introductionmentioning
confidence: 78%
“…Immediately after seizure testing, mice were euthanized with an overdose of ketamine/xylazine, and the brains were removed and frozen on dry ice. Quantitative Western blotting was performed on whole forebrain homogenates as described previously (Adusei et al, 2010). The following antibodies were used: mouse anti-GABA B R1 (clone NR3A/49; 1:250; NeuroMab, University of California, Davis, CA/National Institutes of Health, Bethesda, MD); mouse anti-GABA B R2 (clone N81/2; 1:750; NeuroMab, University of California, Davis/National Institutes of Health); rabbit antimGluR5 (1:500; Millipore Bioscience Research Reagents, Temecula, CA); mouse anti-GAPDH antibody (1:40,000 -1:100,000; SigmaAldrich); and a goat anti-mouse (The Jackson Laboratory, Bar Harbor, ME) or goat anti-rabbit (Thermo Fisher Scientific, Waltham, MA) horseradish peroxidase-conjugated secondary antibody.…”
Section: Animalsmentioning
confidence: 99%
“…Impaired GABAergic signaling in FXS might partially be caused by decreased expression of GABA receptors in these brain areas (El Idrissi et al, 2005;D'Hulst et al, 2006;Adusei et al, 2010). On the other hand, it could be a secondary effect of dysregulated mGlu 1/5 -dependent signaling, because these two receptors were shown to crosstalk in several different brain areas (Hirono et al, 2001;Deng et al, 2010;Kolaj and Renaud, 2010).…”
Section: Altered Signaling Of Other Membrane Receptorsmentioning
confidence: 99%
“…These altered behaviors are accompanied by a series of anatomical and synaptic plasticity deficits, mainly affecting neurotransmission at the level of GABA A and group I metabotropic glutamate (mGluR1/5) receptors. Several studies showed a severe reduction in the expression of GABA A receptor subunit mRNAs and proteins in adult Fmr1 KO mice [2,49], along with an abnormal GABAergic transmission [27,43] and deficits of parvalbumin (PV) expressing cortical GABAergic interneurons [125]. A "metabotropic glutamate receptor (mGluR) theory" of FXS pathogenesis has also been proposed, based on a series of findings indicating that in the absence of FMRP, the FMRP-dependent consequences of mGluR5 activation are exaggerated [10].…”
Section: Fmr1mentioning
confidence: 99%